Hydraulic endorectal actuator for prostate radiotherapy reduces variations in motion in a silicone rectal phantom - Niknam Maleki, Aryan; Runciman, Mark; Murray, Julia; Mylonas, George (Frontiers in Oncology, 2026)
BackgroundThe accuracy and morbidity of prostate cancer radiotherapy are influenced by unpredictable variations in rectal filling and patient motion. We developed a soft robotic hydraulic endorectal actuator that aims to reduce rectal motion and retract the rectum to restore the anorectal angle, improve target accuracy, and reduce toxicity during prostate cancer radiotherapy. The ability of the endorectal actuator to stabilize the rectum and improve prostate radiotherapy outcomes has not yet been assessed. This study evaluates the actuator’s performance in a simulated rectal phantom.MethodsWe fabricated a rectal phantom using silicone and motor-controlled elastic ribbons to simulate muscle tone and control the phantom diameter. The rectal compliance of the phantom was validated using a barostat balloon and was deliberately set low to simulate a high resistance to distension to challenge the actuator’s capabilities. We assessed the actuator’s ability to (1) resist dynamic peristaltic forces and (2) reproduce the rectal position and anorectal angle from varying initial displacements. The anterior–posterior rectal diameter and anterior rectal wall (ARW) displacements were measured using video tracker software.ResultsThe phantom demonstrated a rectal compliance of 4.19 ml/mmHg within the 40 ml–60 ml volume range, meeting the low-compliance target. During dynamic compression, the endorectal actuator reduced the change in the anterior–posterior diameter and ARW displacement from 25 mm and 15 mm, respectively, to less than 5 mm in both. The actuator reduced the increase in rectal volume from 132.3 cm3 (control) to 59.7 cm3 (actuator). When the phantom was translated anteriorly, the actuator reduced the anorectal angle deviation from +12° to +2° and anterior displacement of the ARW from 13 mm to 4 mm.ConclusionWithin this rectal phantom, the endorectal actuator reduced the variations in rectal motion. These findings suggest that the actuator may improve target accuracy and reduce radiation-induced toxicity in prostate radiotherapy, pending in vivo validation of the results.